Análise dialélica de Jinks & Hayman em genótipos de algodoeiro - Vieira, Fernanda Almeida de Carvalho (2006)
This research aimed at the estimation of genetic parameters in a diallel cross according to the methodology developed by Jinks & Hayman. The experiment was conducted in an experimental area of the Agronomy Dept. of the ILES/ULBRA University, at Itumbiara, Goiás, Brazil in 2003. Treatments tested comprised the eight parental cultivars and their 28 hybrid combinations. The following traits were submitted to the J&H analysis: cottonseed yield, lint yield, picked lint percent, seed index, index of production and earliness, fiber strength, uniformity of length, short fiber index, CSP index and reflectance. With the exception of the latter, all other traits presented variability among treatments based on the anova. Fiber length and elongation, failed to meet at least one of the assumptions of the additive dominant genetic model for the analysis and therefore were not considered further. The higher values of heritability in both narrow and broad sense were estimated for the trais lint percent and seed index. The parental genotypes Antares and CD-403 were found to be the most indicated for the improvement of the majority of the agronomic traits. On the other hand, DeltaOpal was the one indicated for the improvement of most fiber traits.